The state and trends of the labor market in the Russian Federation - A. S. Obukhova; A. I. Piyaltsev (Вестник Северо-Кавказского федерального университета)
The issues of functioning and development of the labor market are particularly relevant in modern socio-economic and geopolitical conditions of financial and economic activity. The influence of various external and internal factors, the emergence of new threats and challenges necessitate the study of ongoing changes and the formation of an effective set of tools and methods for the development of the labor market. The coronavirus pandemic and the introduction of unilateral sanctions against the Russian economy by a number of foreign countries have become one of the most serious negative factors that have influenced the state and trends in the development of the Russian labor market over the past 5 years. The article studies the dynamics of indicators reflecting the levels of employment and unemployment, wages, the number of organizations, small and medium-sized businesses, individual entrepreneurs for 2017–2021. The information base for the research is the official websites of the Federal State Statistics Service, the Federal Tax Service, the results of the work of scientists, researchers and experts in this field. The authors note and assess the nature and extent of the impact of the coronavirus pandemic on the Russian labor market. A decrease in the employment rate, an increase in the unemployment rate, and a slowdown in the growth of monetary incomes of the population in 2020 were revealed. The introduction of coronavirus restrictions also led to a decrease in the economic and investment activity of the population and economic entities as a whole. The key role in solving the problems that have arisen in the conditions of the impact of the coronavirus pandemic on the labor market is played by the state, developed and implemented targeted support measures. According to the results of the study, the authors made the conclusions and recommendations.